História, presságios memoráveis e a morte do Imperador Juliano na obra de Amiano Marcelino (390-392 d.C.) - Carvalho, Margarida Maria De [UNESP] (Universidade Estadual Paulista Julio de Mesquita Filho, 2020)
In this article, I’d like to analyze the books XXIII-XXV of Ammianus Marcellinus’ Res Gestae, about the crucial moments of the war between Romans and Persians. At the same time, I intend to understand Julian’s death in the battle against these enemies. This style is a part of the bellum gender, illustrated by Sallustius (86-35 BC) and Iulius Caesar (100-44 BC). It’s also included in the imperial biography style, whose development occurred until the Late Antiquity. I’ll interpret the episodes that happened before and after the death of the Emperor Julian in the vision of this military writer. This text will be based in the methodology of the History of Emotions. In this way, I want to stand out sentiments like fear and courage that blend together in the course of the narrative.

Neste artigo, temos a intenção de analisar os livros XXIII a XXV da obra Res Gestae de Amiano Marcelino, a respeito dos momentos cruciais da guerra contra os persas e da morte de Juliano no meio de uma batalha contra esses adversários. Esse estilo faz parte do gênero romano do discurso bellum, ilustrado por Salústio (86-35 a.C.) e Júlio César (100-44 a.C.), assim como o estilo da biografia imperial cujo desenvolvimento ocorreu até a Antiguidade Tardia. Pretendemos interpretar episódios que ocorreram antes e durante a morte do Imperador Juliano na visão desse autor militar. O texto será desenvolvido tendo como base a metodologia da História das Emoções. Dessa forma, serão ressaltados sentimentos como o medo e a coragem que se mesclam no decorrer da narrativa.
History, Memorable Omens and the Death of the Emperor Julian in Ammianus Marcellinus’ Work (390-392 AD)
Keywords: History; Omens; Death; Julian; História; Presságios; Morte; Juliano